Emiliusz Paulus w podróży po Grecji = Aemilius Paullus tours Greece - Appel, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Following the Battle of Pydna, the victorious general Lucius Aemilius Paullus embarked on a trip of Greece . Accounts of the event may be found in Polybius, Livy and Plutarch. Each of them focused on different aspects of that journey. The most extensive surviving report is provided in Livy's Ab Urbe Condita (45, 27-28), which is therefore the basic reference for the analysis conducted by the author in this paper.
Keywords: Lucius Aemilius Paulus Macedonicus (227-153 p.n.e.); Bitwa 168 p.n.e. pod Pydną; podróże w starożytności; Olimpia; Delfy; filhellenizm; fryz płaskorzeźbiony w Delfach; pobożność Emiliusza Paulusa; ancient travel; Olympia; Delphi; philhellenism; relief frieze at Delphi; Battle of Pydna (168 p.n.e.); piety of Aemilius Paullus